Bank Responsibilities in Guaranting Customer Data at Bank Syariah Indonesia of Lhokseumawe City - Sulaiman Sulaiman (Malikussaleh Social and Political Reviews, 2023)
Leakage of customers' personal information data is a recurring problem in Indonesia, which impacts both state-owned and private banks. Leaks occur due to various internal and external factors, creating a significant data misuse risk. To overcome this problem, Law Number 27/2022 concerning the Protection of Personal Data emphasizes the importance of protecting personal information and ensuring proper use. This study investigates the responsibility of Bank Syariah Indonesia in the city of Lhokseumawe in protecting customer data, identifies factors contributing to data breaches, and proposes steps to mitigate the incident. By using empirical normative juridical research methods, this research used a law-based and case-based approach. The findings revealed that Bank Syariah Indonesia Lhokseumawe also experienced data breaches, mainly due to internal and external factors. The actions of bank employees cause internal leaks, while external factors include individuals involved in fraudulent activities to exploit customer data. Urgent action must be taken to effectively address data breaches, including comprehensive security protocols, staff training, and cooperation with relevant authorities. By adhering to these steps, banks can strengthen their data protection practices and effectively mitigate the risks associated with data breaches.